Treatment of Cognitive and Behavioral Disorders in Children Using Transcranial Magnetic Stimulation: Literature Review - Julia V. Nesterova; George A. Karkashadze; Leila S. Namazova-Baranova; Elena A. Vishneva; Elena V. Kaytukova; Leonid M. Yatsik; Daria A. Bushueva; Natalia S. Sergienko; Tinatin Yu. Gogberashvili; Tatiana A. Konstantinidi; Dmitry S. Kratko (Union of pediatricians of Russia, 2021)
Speech disorders have the leading position among cognitive disorders and represent the urgent medical problem. The modern approach to the treatment of cognitive and behavioral disorders in children consists of the integrity of pharmacotherapeutic, correctional and psychotherapeutic, as well as non-invasive instrumental methods of brain neurostimulation. This article provides the overview of the currently available data on transcranial magnetic stimulation method as noninvasive treatment of various neuropsychiatric disorders in children and its difference from physiotherapeutic methods used in traditional Russian practice.